Evaluating Three Approaches To Enhance Oral Hygiene In Adult Orthodontic Patients - Muhammad Abdullah kamran; Ziad Abdulrahman Alshehri; Naif Mohammed Alzahrani; Hohammed hassan asiri; Abdullrhman nasser leslom; Muidh Mohammed Faleh Alasmari; Abdulaziz Alshahrani (KARACHI MEDICAL AND DENTAL COLLEGE, 2024)
Objective: To compare outcomes in terms of the Bleeding index, Gingival Index and Orthodontic Plaque Index with videographic and plaque disclosing tablets versus verbal instructions in adult orthodontic patients undergoing fixed appliance treatment. Methods: This randomized control study was conducted at King Khalid University, Dept. of Orthodontics. Adult orthodontic patients are recruited from outpatient orthodontic clinics who fulfilled the inclusion criteria and total 60 participants were randomly allocated to three groups.  Subjects having > 2 mm of clinical attachment loss, pregnant and lactating females, any history of periodontal therapy within the last six months, and any consumption of antibiotics or anti-inflammatory drugs within the last month were excluded. The outcomes in terms of the Bleeding Index, Gingival Index, and Orthodontic Plaque Index with videographic and plaque-disclosing tablets(PDT) versus verbal instructions' were recorded using a standardized technique. Data were analyzed using SPSS version 26.00. Results: The study involved 60 participants with a maximum mean age of 21.15 ± 6.27 in the verbal respondent group with higher proportion of men. There was no significant difference found between the three groups and genders for baseline and after-treatment mean scores for Bleeding Index, Gingival Index, and Orthodontic Plaque Index. However, pre-and post-interventional changes were evaluated using a paired t-test, which produced statistically significant results for the verbal, video, and PDT groups in lower jaw as well as the video and PDT groups in the upper jaw. Simple linear regression model suggests that video plays a significant role in improving oral hygiene, and the video group is more effective in educating about oral hygiene. Conclusion: In conclusion, videographic and PDT methods appear to be effective in improving oral hygiene outcomes in adult orthodontic patients undergoing fixed appliance treatment.